Analisis Efek Media Massa terhadap Perubahan Perilaku dan Struktur Nilai Kultural di Masyarakat - Rizky Fadilah; Marissa Zefrina; Ummi Salma; Kholis Ridho (Bahasa Indonesia, 2025)
This study investigates the effects of mass media on behavioral changes and cultural value structures in society. Mass media plays a crucial role as a source of information and an agent of social transformation, influencing cognitive, affective, and conative aspects of individuals and communities. This research draws on mass communication theories and previous studies to explore how media fosters changes in public perceptions, attitudes, and behaviors, while also highlighting its dual impact both positive and negative. The urgency of this study lies in addressing the growing reliance on media in the digital age and the necessity of critical media literacy among audiences. Using a qualitative approach, data was collected through questionnaires and in-depth interviews to capture audience experiences and their interactions with media. Findings suggest that media significantly shapes societal norms, influencing lifestyle choices, cultural identity, and social awareness. However, unchecked media influence can perpetuate stereotypes, misinformation, and cultural homogenization. The study concludes by advocating for increased critical awareness and education in media literacy to empower audiences to filter media messages effectively and encourage sustainable social change.